Manajemen Mutu Peserta Training - Riana Dewi; Veithzal Rivai Zainal; Lenny Nawangsari (Publikasi Indonesia, 2022)
A system is a foundation or foothold for an organization or company in carrying out its activities or operations. Without a compact and solid system, an organization or company will stagnate and even die. However, a system is not enough, it takes the name of strategic management that can increase the strength of the company or organization itself, and also in running its business. The strategy developed by the organization through the strategic management process aims to create competitive advantages for the organization. This study uses qualitative research methods and it can be shown that this company uses the concept of strategic management because it is more profitable than companies that do not apply strategic management. strategic management is the highest management activity prepared by the top brass of an organization or company, which is then followed up by the executive team. An organization or company has a hierarchy of strategies (levels of strategy) in it, namely from the corporate level to the level of implementing activities.